Pengaruh Penambahan Maizena Terhadap Kadar ΒetaKaroten, Aktivitas Antioksidan Dan Sifat Organoleptik Sup Labu Kuning Instan - Dian Eka Rahma Yulianti; Nurrahman Nurrahman; Wikanastri Hersoelistyorini (Jurnal Pangan dan Gizi, 2020)
Yellow pumpkin is one of the agricultural products that contain beta-carotene and high antioxidant compounds so it is good for body health. Pumpkin processed into Instant yellow pumpkin soup with added cornstarch and set flour formulation Maize is the best for instant soup. The purpose of this study was to determine the effect of maize addition to beta-carotene levels, antioxidant activity and organoleptic instant yellow pumpkin soup. The factor of this research is the addition treatment cornstarch (0%, 2%, 4%, 6%). Tests carried out are beta-carotene levels, antioxidant activity, and organoleptic (color, aroma, taste, texture). Results research that has been done, obtained the best levels of antioxidants (12.90%) in the sub pumpkin instant yellow with the addition of cornstarch 4%, the best content of beta-carotene (43.20 ppm) in the instant yellow pumpkin sub with the addition of 4% cornstarch, and organoleptic properties (color, aroma, taste, and texture with a degree of liking) best on the yellow pumpkin sub instant with the addition of cornstarch 4%. Moisture content of 10.45%, ash content of 1.12%, 6.72% protein content, 11.01% fat content, 16.16% fiber content, and total carbohydrate by 54.54%.